Karakterisasi Kompleks Inklusi Simvastatin – Β-Siklodekstrin Metoda Co-Grinding dengan Variasi Waktu Penggilingan - Maria Dona Octavia; Auzal Halim; Monica Afrinda (STIFARM Padang, 2015)
Characterization of simvastatin - b-cyclodextrin inclusion complexes by co-grinding method had been studied. Solid state simvastatin - b-cyclodextrin inclusion complex prepared by co-grinding method in 1:1 mol ratio. Simvastatin, b-cyclodextrin, simvastatin - b-cyclodextrin physical mixture and inclusion complexes were characterization by X-ray Diffraction (XRD), Fourier Transformation Infra red (FTIR), Differential Thermal Analysis (DTA), scanning electron microscope (SEM) and dissolution studies. X-Ray Diffraction results showed decreasing peak intensity diffractogram very sharp compared to pure simvastatin and differential thermal analysis (DTA) were showed the interaction between simvastatin and b-cyclodextrin. In vitro dissolution rate studies of simvastatin, simvastatin - b-cyclodextrin physical mixture and inclusion complexes. Simvastatin - b-cyclodextrin inclusion complex showed increasing dissolution rate significant compared to simvastatin - b-cyclodextrin physical mixture and pure simvatatin. The results showed the formation of inclusion complex between simvastatin and b-cyclodextrin by co-grinding method.